2017
DOI: 10.18805/ijar.b-3291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mannan-oligosaccharides (MOS) supplementation on performance, immunity and HSP70 gene expression in broiler chicken during hot-dry summer

Abstract: An experiment was conducted on broiler chicks (n=120), reared in cages on a standard diet up to 14 th day of age and thereafter up to 42 nd day (14-42d) on test diets with or without MOS. The 14 th day old chicks were randomly distributed into three dietary treatment groups viz., T 1 (control diet), T 2 (control diet with MOS @ 0.3%) and T 3 (control diet with MOS @ 0.5%). Each dietary treatment comprised of four replicates of eight birds each. Experiment was carried out during hot-dry summer. It was found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
5
0
1
Order By: Relevance
“…The above results are consonant with those of Mousa et al [17]. Meanwhile, Yalçinkaya et al [21] found a significant decrease in the [22], who found a significant increase in the serum activities of AST and ALT, and protein concentration in broilers dietary supplemented with MOS. These results may be attributed to the antioxidant properties of the MOS, which was reported by Dawood et al [11].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The above results are consonant with those of Mousa et al [17]. Meanwhile, Yalçinkaya et al [21] found a significant decrease in the [22], who found a significant increase in the serum activities of AST and ALT, and protein concentration in broilers dietary supplemented with MOS. These results may be attributed to the antioxidant properties of the MOS, which was reported by Dawood et al [11].…”
Section: Discussionsupporting
confidence: 87%
“…The colonization of E. coli in the control infected group in different organs showed several rates of 67, 44, 22, 44, and 53% in the respiratory tract, liver, gallbladder, spleen, and fecal swab, respectively (see Table 6). However, in the agrimos infected group, the colonization of E. coli in different organs showed reduced rates of 22,33,22,11, and 33% in the respiratory tract, liver, gallbladder, spleen, and fecal swab, respectively.…”
Section: Colonization Of E Colimentioning
confidence: 88%
“…[13] found a significant decreased AST and ALT activities but Rokade et al [14] found significant increased AST and ALT activities and protein concentration of the serum in broilers dietary supplemented with MOS. On the other hand, results of antioxidant enzymes and MDA in harmony with results of Zhou et al [15] who found significant decrease of antioxidant enzymes in birds infected with necrotic enteritis.…”
Section: Discussionmentioning
confidence: 99%
“…The prebiotic evaluated in the present study is composed of yeast cell wall components (MOS), and fermented Bacillus subtilis components. Dietary supplementation of MOS in poultry diets with or without AGP has been shown to have positive benefits in terms of performance, immune modulation, and reduction of pathogens (37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%